Changes in Smoking Behavior over Family Transitions: Evidence for Anticipation and Adaptation Effects - Bricard, Damien (Int J Environ Res Public Health, 2017)
The study of changes in smoking behaviors over the life course is a promising line of research. This paper aims to analyze the temporal relation between family transitions (partnership formation, first childbirth, separation) and changes in smoking initiation and cessation. We propose a discrete-time logistic model to explore the timing of changes in terms of leads and lags effects up to three years around the event in order to measure both anticipation and adaptation mechanisms. Retrospective biographical data from the Santé et Itinéraires Professionnels (SIP) survey conducted in France in 2006 are used. Partnership formation was followed for both genders by a fall in smoking initiation and an immediate rise in smoking cessation. Childbirth was associated with increased smoking cessation immediately around childbirth, and additionally, females showed an anticipatory increase in smoking cessation up to two years before childbirth. Couple separation was accompanied by an anticipatory increase in smoking initiation for females up to two years prior to the separation, but this effect only occurred in males during separation. Our findings highlight opportunities for more targeted interventions over the life course to reduce smoking, and therefore have relevance for general practitioners and public policy elaboration.